Operation of Wearable Thermoelectric Generators Using Dual Sources of Heat and Light - Myeong Hoon Jeong; Kwang-Chon Kim; KIM, JIN SANG; Kyoung Jin Choi (WILEY, 2022)
A wearable thermoelectric generator (WTEG) that utilizes human body heat can be a promising candidate for the wearable power generators. The temperature difference (Delta T) between the body and the environment is a stable source driving the WTEG, but this driving force is limited by the ambient temperature itself at the same time. Here, a novel WTEG that can be operated using the dual source of body heat and light with exceptionally high driving force is fabricated. The printable solar absorbing layer attached to the bottom of the WTEG absorbs approximate to 95% of the light from ultraviolet to far infrared and converts it into heat. To optimize the power density of WTEGs, the fill factor of the thermoelectric (TE) leg/electrode is considered through finite-difference time-domain (FDTD) simulation. When operated by the dual sources, the WTEG exhibits a power density of 15.33 mu W cm(-2), which is the highest under "actual operating conditions" among all kinds of WTEGs. In addition, unlike conventional WTEGs, the WTEG retains 83.1% of its output power at an ambient temperature of 35 degrees C compared to its output power at room temperature. This study will accelerate the commercialization of WTEGs by introducing a novel method to overcome their limitations.